Conversation proficiency assessment : a comparative study of two-party peer interaction and interview interaction implemented with Thai EFL learners - Ratchawan Ussama (Prince of Songkla University, 2014)
Thesis (M.A.TEIL., Teaching English as an International Language)--Prince of Songkla University, 2013